2014
DOI: 10.5614/j.eng.technol.sci.2014.46.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of SH-Wave Amplification in the Bandung Basin Using Haskell’s Method

Abstract: The Bandung basin is a large basin in Indonesia surrounded by mountains that are associated with faults. There is the possibility of earthquakes generated by these faults shaking populated areas in the basin. The consequences will be worse because the shaking is amplified by the sediment layer of the basin. We have estimated the amplification of SH-waves generated by the Lembang fault using Haskell's method for multilayer models. The pattern of amplification is a decreasing value with increasing distance from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Akan tetapi dalam pembahasan seismotektonik kita mengharapkan informasi hiposenter berada tepat pada sistem patahan yang ada sesuai dengan kondisi tektonik yang ada serta penyimpangan yang lebih kecil. Relokasi gempabumi biasanya digunakan untuk melakukan identifikasi zona patahan berdasarkan distribusi gempa yang terjadi, sehingga dapat dipahami kondisi tektonik wilayah tersebut (Afnimar, 2009). Salah satu metode relokasi yang sering digunakan adalah Metode Double Difference.…”
Section: Pendahuluanunclassified
“…Akan tetapi dalam pembahasan seismotektonik kita mengharapkan informasi hiposenter berada tepat pada sistem patahan yang ada sesuai dengan kondisi tektonik yang ada serta penyimpangan yang lebih kecil. Relokasi gempabumi biasanya digunakan untuk melakukan identifikasi zona patahan berdasarkan distribusi gempa yang terjadi, sehingga dapat dipahami kondisi tektonik wilayah tersebut (Afnimar, 2009). Salah satu metode relokasi yang sering digunakan adalah Metode Double Difference.…”
Section: Pendahuluanunclassified
“…The sediment structure has been investigated using the microtremor array method [5], which showed that the deepest basement reaches about 3.5 km. Seismic wave amplification in the Bandung Basin was simulated by Afnimar [6] using Haskell's method.…”
Section: Backgorundmentioning
confidence: 99%
“…The analysis also detected the presence of a suspected active fault area which was not identified on the geological map. (Afnimar, 2009).…”
Section: Abstract Abstract Focal Mechanism Fault Rupturementioning
confidence: 99%